The Development Trend of Digital Research on China's Intangible Cultural Heritage in the Past Decade —Based on CNKI Knowledge Graph Analysis (Journal of Global Arts Studies, 2025)
Background: In the past decade, against the backdrop of cultural confidence in the new era, the academic research perspectives in the fields of protection, dissemination and utilization of China's intangible cultural heritage digitalization have become increasingly diversified. Objective: This paper aims to study the development trend of digital research on China's intangible cultural heritage in the past decade. Methods: This study uses CiteSpace software to search the core journals related to the digitization of China's intangible cultural heritage included in CNKI from January 2015 to March 2025. Through bibliometric and visualization analysis, it summarizes the research results of scholars in this field in the past decade. Results: The study found that in the past decade, the research on the digitization of intangible cultural heritage has shown a research evolution trend of "data integration and application exploration" - "interaction and communication" - "activation and transformation". At the same time, the field of intangible cultural heritage digitization focuses on themes such as "living inheritance" and "digital technology". Conclusion: Under the new circumstances, China's intangible cultural heritage digitalization research will focus on cultivating a compound team of intangible cultural heritage talents, forming a diversified cooperation circle, expanding the digital inheritance path of intangible cultural heritage, building a good intangible cultural heritage ecosystem, integrating and building a public intangible cultural heritage digital innovation platform, and telling the Chinese story of the new era well.
Keywords: IntangibleCulturalHeritage Digitization; KnowledgeGraph; Dissemination; Intangible Cultural Heritage Ecosystem